HUKUM GADAI DALAM ISLAM DAN PRAKTEKNYA DI SULAWESI SELATAN - Sofyan, A. Syathir (Fakultas Syariah Institut Agama Islam Negeri Palu, 2019)
The main problem of this research is how Islam views the Pasanra (pawn) implementation system. This type of research is qualitative The data source of this research is books and literature related to the problem of this topic. The results of the discussion showed that the Pasanra (pawning) system of a pawner (rahin) came to the pawn recipient (murtahin) to borrow money to meet the needs of the garden as collateral. The right to control / use the estate is in the hands of the pawner (murtahin) until the repayment of the debt. Debt payments do not know the time limit and the contract ends when the pawner (rahin) pays the debt according to the amount of money borrowed.